PKM Pondok Pesantren Wisata Al-Quran Pangkep - Sahade Sahade; Muh. Faisal; Bakhrani A. Rauf (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The problems of the Community Partnership Program (PKM) in the Pangkep Regency Islamic Boarding SchoolIslamic Boarding School students (partners) are as follows: (1) The curriculum is mostly religiously loaded, very little is publiclycharged, and there is no skillful skill, for example craft skills in making souvenirs from environmental waste , (2) Knowledge andskills both craft skills and similar skills are very limited, (3) The availability of environmental waste at the location of theapplication of PKM which is a raw material for making various kinds of souvenir crafts by utilizing environmental waste, (4)Limited parties who can train in terms of designing various kinds of souvenirs by utilizing environmental waste, (5) Limitedskills of students (partners) in terms of making and assembling various kinds of souvenirs by utilizing environmental waste, (6)Limited skills of students (partners) in terms of fnishing work various kinds of souvenirs with utilize waste environment, (7)Limited knowledge of santri groups (partners) in terms of entrepreneurship of various kinds of souvenirs by utilizingenvironmental waste. The solution offered by the Community Partnership Program (PKM) at the Pangkep Regency IslamicBoarding School Islamic Boarding School students (partners) is to provide: (1) knowledge of utilizing environmental waste intosouvenirs of various shapes and models. (2) skills in using hand tools and machines in making souvenirs by utilizingenvironmental waste in various shapes and models, (3) skills in preserving environmental waste that will be used as souvenirs,(4) skills in forming souvenirs by utilizing environmental waste, (5) assembling skills souvenirs by utilizing environmentalwaste, (6) skills of finishing souvenir work by utilizing environmental waste, (7) knowledge of marketing the results of variouskinds of souvenirs by utilizing environmental waste. The expected outputs in the Community Partnership Program (PKM) on thestudents of the Pangkep Regency Al-Qur'an Tourism Boarding School (partners) are: (1) having the knowledge of utilizingenvironmental waste into souvenirs of various shapes and models. (2) have skills using hand tools and machines in makingsouvenirs by utilizing environmental waste in various shapes and models, (3) have skills in preserving environmental waste thatwill be used as souvenirs, (4) have skills in forming souvenirs by utilizing environmental waste, (5 ) has the skills to assemblesouvenirs by utilizing environmental waste, (6) the skills of finishing souvenir work by utilizing environmental waste, (7) has theknowledge of marketing the results of various souvenirs by utilizing environmental waste.